2023
DOI: 10.2147/prbm.s411800
|View full text |Cite
|
Sign up to set email alerts
|

Does My Humor Touch You? Effect of Leader Self-Deprecating Humour on Employee Silence: The Mediating Role of Leader-Member Exchange

Abstract: Purpose Silence is a typical negative behaviour exhibited by employees when they are faced with tension and stress and is influenced by a number of factors. Leaders have an important influence on employees’ emotions and behaviour, but the research is not yet clear enough. In this paper, we focus on the research frontier of self-deprecating humour of leaders, aiming to analyse its effect on employee silence and discuss the mechanism of the role of leader-member exchange (LMX) in it, based on social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…An et al, 2023;Cooper, 2008), and the effect of leader humor on employees' organizational citizenship behaviors(Yang & Zhang, 2022). In another meta-analysis, Mesmer-Magnus et al (2012) indicated that employees' sense of humor improves job performance, job satisfaction, group cohesion, and physical health and mitigates occupational fatigue and stress.…”
mentioning
confidence: 99%
“…An et al, 2023;Cooper, 2008), and the effect of leader humor on employees' organizational citizenship behaviors(Yang & Zhang, 2022). In another meta-analysis, Mesmer-Magnus et al (2012) indicated that employees' sense of humor improves job performance, job satisfaction, group cohesion, and physical health and mitigates occupational fatigue and stress.…”
mentioning
confidence: 99%